Diffuse lesions in the limbic system with short‐term memory loss in a patient with multiple sclerosis. (8th March 2018) - Takai, Yasuyuki; Warabi, Yoko; Norioka, Ryohei; Tojima, Maya; Ikezawa, Jun; Okiyama, Ryoichi; Isozaki, Eiji
Abstract: Background: The role of B cells in the pathogenesis of multiple sclerosis (MS) is a subject of much research. We report a case of a MS patient who presented with subacute diffuse lesions in the limbic system and short‐term memory loss. Case presentation: A male patient had experienced numbness in the left upper extremity at the age of 17 years, but this disappeared without treatment. At 19 years‐of‐age, he developed subacute short‐term memory loss followed by paralysis and sensory disturbance in the left upper and lower extremities. Magnetic resonance brain fluid‐attenuated/T2‐weighted imaging showed diffuse high‐intensity lesions in the medial parts of both temporal lobes, and spotty multiple lesions in the periventricular and subcortical white matter. Twenty days later, a new lesion was observed around the right putamen, and the temporal lesions had disappeared. A symptomatic cervical lesion with gadolinium enhancement was observed at C3. This lesion involved just one vertebral segment. Cerebrospinal fluid analysis showed no pleocytosis or elevated protein levels, but did show oligoclonal immunoglobulin G bands. No antibodies against aquaporin‐4 or myelin oligodendrocyte glycoprotein were detected in the serum, and anti‐N‐methyl‐D‐aspartate receptor was not detected in the cerebrospinal fluid. We diagnosed the patient with MS despite the atypical diffuse lesions in the limbic system and the short‐term memory loss. Corticosteroid medication effectively treated the symptoms in his extremities and his impaired memory. Conclusions: The present case shows that cortical lesions can occur in MS patients and might be induced by B cell‐mediated mechanisms.